A Multidisciplinary Experimental Study on the Effects of Breeders Diet on Newborn Seahorses (Hippocampus guttulatus) - Planas, Miquel; Olivotto, Ike; González, María Jesús; Laurà, Rosaria; Zarantoniello, Matteo (Frontiers in Marine Science, 2020)
The global trade in seahorses is increasing and new rearing techniques are currently available for a few species. One of the main bottlenecks in seahorse production is reproductive success, which is dependent upon the administration of high quality diets to breeders. However, little is known about the most adequate diets, on how they should be administered and on how they might affect newborn performance. In this study, three homogeneous groups of adult seahorses Hippocampus guttulatus were maintained in captivity. Each group was fed on one of the following diets since the onset of the breeding period: unenriched adult Artemia (Diet A), unenriched adult Artemia and mysidaceans (Diet AM) and mysidaceans (Diet M). As a positive control, a wild pregnant male was used. The mixed diet AM provided the highest overall breeding success and reasonable fatty acid profiles, and better resembled newborn from a wild male. The use of mysidaceans solely (Diet M) provided the worse results in spite of the high DHA content. Significant differences were observed in newborn characteristics and fatty acid profiles among dietary groups and along the breeding season, especially in total n-3 HUFA and DHA. Monospecific diets including Artemia or mysidaceans very likely suffered nutritional deficiencies, which were reflected in morphological alterations of the muscle tissue (diet A) or abnormal early mortalities in newborn (diet M). Three progressive stages were identified along the whole breeding period: initial mixed capital-income period (100 – 120 days since the onset of the breeding period), followed by an inflexion period (short transitional stage - income sources), and finally a long period characterized by the use of income sources and the progressive exhaustion of body reserves. Special attention should be deserved to the progressive changes in fatty acid profiles along the breeding season, resulting in a decrease in newborn performance. Considering the time required for a diet to be reflected in newborn, we recommend Hippocampus guttulatus breeders to be fed on a high quality diet for at least three months prior the breeding period.